Examining the Intersections of Family Risk, Foster Care, and Outcomes for Commercially Sexually Exploited Children - Courtney Furlong; James Benjamin Hinnant (Social Sciences)
Purpose: When individuals under the age of 18 are victimized by sex trafficking, it is termed commercial sexual exploitation of children (CSEC) in the United States. It is suggested that a history of engagement with the foster care system is one of the leading risk factors for CSEC. However, it is possible that it is the very factors that facilitate engagement with the foster care system (e.g., neglect, abuse, etc.) that establish vulnerability for CSEC victimization rather than the foster care system itself and that the foster care system serves a protective role for such victims. The purpose of this investigation is to examine the relationship between risk factors within the family of origin, foster care experiences, and outcomes for CSEC victims. Methods: Between 2014 and 2023, data were collected on minor victims of CSEC (n = 884) via the Child and Adolescent Needs and Strengths Assessment for Commercial Sexual Exploitation (CANS-CSE). Investigators conducted regression analyses to examine the relationship between family risk and foster care engagement (Aim 1). Foster care engagement (Aim 2) and number of foster care placements (Aim 3) are tested as moderators of associations between family risk factors and outcomes for youth. Results: Family risk is significantly associated with negative outcomes. Foster care placement and number of foster care placements do not moderate the link between family risk factors and negative outcomes for victims of CSEC. Conclusions: Results suggest that foster care does not protect against risks associated with families of origin and negative outcomes, a finding that may be unique for CSEC victims. Therefore, specialized, trauma-informed services should be implemented with CSEC victims who are engaged in the foster care system. In doing so, foster care could begin to serve a protective role in supporting young victims of CSEC and producing more positive outcomes.